2014
DOI: 10.4103/0255-0857.129802
|View full text |Cite
|
Sign up to set email alerts
|

Clinicomicrobiological analysis of patients with cholangitis

Abstract: Acute cholangitis is inflammation of biliary ductal system from infection with an associated biliary obstruction. This retrospective study was done to determine the factors responsible for cholangitis and the microbiological profile of the bile in patients with cholangitis. In the study involving 348 patients, 36.4% had associated malignancy. A total of 54% of the bile samples were positive for aerobic culture. Nearly 66-73% of the Escherichia coli and Klebsiella isolates were Extended spectrum beta lactamases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
6
23
1
Order By: Relevance
“…A prospective cohort study in patients with acute cholecystitis involving 116 institutions worldwide showed that among 96 isolated E. coli , 16 (16.7%) were producing ESBL . However, the proportion of ESBL producing E. coli varies widely region to region: 31.2% in two German university hospitals , 70.0% in Korean university medical center and 66% in Indian medical college hospital . There are few reports about the prevalence of carbapenem resistant bacteria specifically among patients with acute cholangitis and cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study in patients with acute cholecystitis involving 116 institutions worldwide showed that among 96 isolated E. coli , 16 (16.7%) were producing ESBL . However, the proportion of ESBL producing E. coli varies widely region to region: 31.2% in two German university hospitals , 70.0% in Korean university medical center and 66% in Indian medical college hospital . There are few reports about the prevalence of carbapenem resistant bacteria specifically among patients with acute cholangitis and cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of antibiotics should include those with a broad range of antimicrobial activity with good penetration into the bile ducts. Examples include thirdgeneration cephalosporins, ureidopenicillins, carbapenems, and fluoroquinolones [31].…”
Section: Variant 2: Initial Therapeutic Procedures For a Patient With mentioning
confidence: 99%
“… 84 For the best practice, administrated antibiotics for cholangitis should be those with broad range antimicrobial activities and which are capable of passing into the bile duct, such as third-generation cephalosporins, ureidopenicillins, carbapenems and fluoroquinolones. 86 The most effective antibiotics for cholangitis patients have been noted as imipenem-cilastatin, meropenem, amikacin, cefepime, ceftriaxone, gentamicin, piperacillin-tazobactam and levofloxacin. 87 , 88 …”
Section: Antibiotics For Cholangitismentioning
confidence: 99%
“…The rates of polymicrobial-positive cultures in AC vary from 30–78%, 86 , 89 , 90 and the response rate to antibiotics in AC is satisfactory in the majority of patients. 40 The achievement of effective antibiotic therapy for AC decreased the death rate of this condition dramatically during the 1970s through 1980.…”
Section: Antibiotics For Cholangitismentioning
confidence: 99%
See 1 more Smart Citation